Left Ventricular Mass Change After Anthracycline Chemotherapy. (July 2018) - Jordan, Jennifer H.; Castellino, Sharon M.; Meléndez, Giselle C.; Klepin, Heidi D.; Ellis, Leslie R.; Lamar, Zanetta; Vasu, Sujethra; Kitzman, Dalane W.; Ntim, William O.; Brubaker, Peter H.; Reichek, Nathaniel; D'Agostino, Ralph B.; et al.
Abstract : Background: Myocardial atrophy and left ventricular (LV) mass reductions are associated with fatigue and exercise intolerance. The relationships between the receipt of anthracycline-based chemotherapy (Anth-bC) and changes in LV mass and heart failure (HF) symptomatology are unknown, as is their relationship to LV ejection fraction (LVEF), a widely used measurement performed in surveillance strategies designed to avert symptomatic HF associated with cancer treatment. Methods and Results: We performed blinded, serial assessments of body weight, LVEF and mass, LV-arterial coupling, aortic stiffness, and Minnesota Living with Heart Failure Questionnaire measures before and 6 months after initiating Anth-bC (n=61) and non–Anth-bC (n=15), and in 24 cancer-free controls using paired t and χ 2 tests and multivariable linear models. Participants averaged 51±12 years, and 70% were women. Cancer diagnoses included breast cancer (53%), hematologic malignancy (42%), and soft tissue sarcoma (5%). We observed a 5% decline in both LVEF ( P <0.0001) and LV mass ( P =0.03) in the setting of increased aortic stiffness and disrupted ventricular-arterial coupling in those receiving Anth-bC but not other groups ( P =0.11–0.92). A worsening of the Minnesota Living with Heart Failure Questionnaire score in Anth-bC recipients was associated with myocardial mass declines ( r =−0.27; P <0.01) but not with LVEF declines ( r =0.11; P =0.45). Moreover, this finding was independent of LVEF changes and body weight. Conclusions: Early after Anth-bC, LV mass reductions associate with worsening HF symptomatology independent of LVEF. These data suggest an alternative mechanism whereby anthracyclines may contribute to HF symptomatology and raise the possibility that surveillance strategies during Anth-bC should also assess LV mass. Abstract : Supplemental Digital Content is available in the text.